2013
DOI: 10.1186/1475-2891-12-56
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of low-fat dairy foods for 6 months improves insulin resistance without adversely affecting lipids or bodyweight in healthy adults: a randomized free-living cross-over study

Abstract: BackgroundGiven the highly debated role of dairy food consumption in modulating biomarkers of metabolic syndrome, this study was conducted to examine the influence of long-term (6 month) dairy consumption on metabolic parameters in healthy volunteers under free-living conditions without energy restriction.MethodsTwenty-three healthy subjects completed a randomized, crossover trial of 12 months. Participants consumed their habitual diets and were randomly assigned to one of two treatment groups: a high dairy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 53 publications
(53 reference statements)
2
72
1
5
Order By: Relevance
“…More recently Maki et al (96) , showed that there was no significant differences in fasting lipoprotein concentrations in sixty-two participants with prehypertension or stage 1 hypertension after 5 weeks of consuming one serving/d of low-fat dairy products compared with non-dairy products. It has also been observed that high dairy product consumption (four servings/d) did not significantly alter blood lipid and lipoprotein responses compared with low dairy product consumption (two servings/d) in twenty-three healthy participants over a 6-month period (97) .…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently Maki et al (96) , showed that there was no significant differences in fasting lipoprotein concentrations in sixty-two participants with prehypertension or stage 1 hypertension after 5 weeks of consuming one serving/d of low-fat dairy products compared with non-dairy products. It has also been observed that high dairy product consumption (four servings/d) did not significantly alter blood lipid and lipoprotein responses compared with low dairy product consumption (two servings/d) in twenty-three healthy participants over a 6-month period (97) .…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
“…Similarly, a number of intervention studies, which specifically investigated the effects of milk and other dairy fats, did not show significantly increased LDL-cholesterol (91)(92)(93)(94)(95)(96)(97) . Furthermore, there is evidence that fermented milk products are hypocholesterolaemic relative to non-fermented equivalents (93,98) .…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited evidence suggests that insulin sensitivity can be improved when dairy consumption is promoted [6,7]. In addition, four meta-analyses of prospective studies have recently reported an overall reduced risk of T2D incidence in subjects with higher dairy consumption, particularly the low-fat variety [8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…A 12-month randomised crossover study comparing high dairy (4 servings/day) or low dairy (no more than 2 servings/day) intake in 23 overweight but otherwise healthy participants found that fasting insulin levels were reduced in the high dairy diet (p < 0.05) thereby reducing insulin resistance (p < 0.05) [25]. Blood pressure, blood lipids, lipoproteins and fasting glucose did not differ between groups and weight and body composition remained stable.…”
Section: Longer Term Dairy Interventions In Overweight Participantsmentioning
confidence: 96%